Impact of uranium uptake on isotopic fractionation and endogenous element homeostasis in human neuron-like cells. Issue 1 (December 2018) - Paredes, Eduardo; Avazeri, Emilie; Malard, Véronique; Vidaud, Claude; Reiller, Pascal; Ortega, Richard; Nonell, Anthony; Isnard, Hélène; Chartier, Frédéric; Bresson, Carole
Abstract The impact of natural uranium (U) on differentiated human neuron-like cells exposed to 1, 10, 125, and 250 µM of U for seven days was assessed. In particular, the effect of the U uptake on the homeostatic modulation of several endogenous elements (Mg, P, Mn, Fe, Zn, and Cu), the U isotopic fractionation upon its incorporation by the cells and the evolution of the intracellular Cu and Zn isotopic signatures were studied. The intracellular accumulation of U was accompanied by a preferential uptake of235 U for cells exposed to 1 and 10 µM of U, whereas no significant isotopic fractionation was observed between the extra- and the intracellular media for higher exposure U concentrations. The U uptake was also found to modulate the homeostasis of Cu, Fe, and Mn for cells exposed to 125 and 250 µM of U, but the intracellular Cu isotopic signature was not modified. The intracellular Zn isotopic signature was not modified either. The activation of the non-specific U uptake pathway might be related to this homeostatic modulation. All together, these results show that isotopic and quantitative analyses of toxic and endogenous elements are powerful tools to help deciphering the toxicity mechanisms of heavy metals.